2011
DOI: 10.1166/jnn.2011.5667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sulfo-Succinimidyl-4-(<I>N</I>-Maleimidomethyl) Cyclohexane-1-Carboxylate Coupling Chemistry for Attachment of Oligonucleotides to Magnetic Nanobeads

Abstract: The sulfo-SMCC (Succinimidyl-4-(N-maleimidomethyl) cyclohexane-1-carboxylate) coupling chemistry was evaluated for immobilization of oligonucleotides onto 130 nm sized magnetic nanobeads aimed for bio-detection in a magnetic readout assay. The chemistry was found to produce a high surface coverage of approximately 93 +/- 10 oligonucleotides per bead whereas stability tests showed that about 50% of the oligonucleotides detached from the bead surfaces after eight weeks of storage in a buffer solution. It was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Zardán Gómez de la Torre et al [ 15 ] later showed that RCA coils can also be detected with a portable AC susceptometer operated at room temperature. [15][16][17][18] Such a device is more compact than a SQUID, but it is still not suitable for the readout in a labon-a-chip biosensor. www.small-journal.com Recently, it has been shown that magnetoresistive planar Hall effect bridge (PHEB) sensors can be used to measure the hydrodynamic size of magnetic nanobeads with no need for externally applied magnetic fi elds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zardán Gómez de la Torre et al [ 15 ] later showed that RCA coils can also be detected with a portable AC susceptometer operated at room temperature. [15][16][17][18] Such a device is more compact than a SQUID, but it is still not suitable for the readout in a labon-a-chip biosensor. www.small-journal.com Recently, it has been shown that magnetoresistive planar Hall effect bridge (PHEB) sensors can be used to measure the hydrodynamic size of magnetic nanobeads with no need for externally applied magnetic fi elds.…”
Section: Introductionmentioning
confidence: 99%
“…However, a SQUID magnetometer is a bulky instrument that requires cryogenic liquids, which makes it unsuitable for the readout in a lab‐on‐a‐chip biosensor. Zardán Gómez de la Torre et al later showed that RCA coils can also be detected with a portable AC susceptometer operated at room temperature . Such a device is more compact than a SQUID, but it is still not suitable for the readout in a lab‐on‐a‐chip biosensor.…”
Section: Introductionmentioning
confidence: 99%
“…The limit of detection (LOD), ∼4 pM, was found to be comparable to that of the SQUID set-up [34]. A covalent conjugation chemistry for attaching detection probes to the magnetic beads relying on the use of a cross-linker reagent (sulfo-SMCC) was employed [37]. The conjugation protocol involved a multi-step procedure requiring rather long time (around a day) and exhibiting modest oligonucleotide coupling yield (at best in the order of a few %).…”
Section: Introductionmentioning
confidence: 99%
“…In the volume‐amplified magnetic nanobead detection assay (VAM‐NDA) this strategy is used in combination with rolling circle amplification (RCA) to achieve a massively enhanced response upon binding of magnetic nanobeads to micrometer‐sized RCA products 12. Previous studies describing the VAM‐NDA principle have mainly focused on the padlock probe mediated detection of DNA 12, 18. In this study, the VAM‐NDA is for the first time applied for detection of proteins through the PLA.…”
mentioning
confidence: 99%